Unstable dorsolumbar fractures: A prospective series of 94 cases - Basheer, N; Gupta, Deepak; Sathyarthi, GD; Aggarwal, Deepak; Sinha, S; Sharma, BS; Mahapatra, AK (Indian Journal of Neurotrauma, 2010)
Dorsolumbar trauma is the most common cause of paraparesis or paraplegia. Optimal goals of the management include establishment of a painless, balanced and stable spinal column with vertebral fusion. We reviewed various types of fractures of dorsolumbar spine, their management and outcome in a prospective study of 94 cases of dorsolumbar trauma managed surgically at our centre (Jan 2008 – May 2009). All patients underwent complete neurological examination, CT and MR imaging of the spine. Most common mode of injury was fall from height (66%). Majority of the patients belonged to Frankel grade A (66 %). Eighteen patients (19 %) were operated using anterior approach and rest by posterior approach. There was no deterioration in neurological status in any of the patients while 26 patients had improvement. Three cases died out of which one was attributed to associated head injury. We conclude that fall from height is the most common cause of dorsolumbar fracture with majority affected belonging to young population and had significant deficits, thus causing significant burden on the society. Surgical management is safe and helps in early mobilization and rehabilitation, thus facilitating possible neurological recovery.
Keywords: dorsolumbar; fracture; paraplegia; transpedicular; rehabilitation